(untitled) (Fiep Bulletin - online, 2012)
Plyometric training is aimed at the development of muscular power using the stretch-shortening cycle (CAE), whichcan be evaluated through the execution of specific jumps. To ascertain the effects of plyometric training in young people 13 to 15years in the development of lower limb strength (explosive force), agility and speed through six weeks of training, underwent aplyometric training program, characterized by leaps vertical, horizontal and depth. The plyometric program was conducted in 15-minute sessions for 6 weeks 2x/week preceded by a physical workout. At the beginning and the end of the study were assessedvertical jump, the horizontal jumping, agility, and speed of displacement and maximum force with an MRI test. The speed of thetested non-significant improvement at the end of six weeks of plyometrics. It was concluded that plyometric training improvedoverall strength and agility of soccer players and has proved an important tool for physical training.